2007
DOI: 10.1073/pnas.0611559104
|View full text |Cite
|
Sign up to set email alerts
|

Role of IFN regulatory factor 5 transcription factor in antiviral immunity and tumor suppression

Abstract: Host defense consists of two main aspects, namely, immune response to invading pathogens and suppression of tumor development. A family of transcription factors, IFN regulatory factors (IRFs), has recently gained much attention in terms of its critical role in linking these two aspects of host defense, wherein IRF5 was previously shown to play a critical role in the induction of proinflammatory cytokines by activation of Toll-like receptors. In the present study, using IRF5 gene-targeted mice (Irf5 ؊/؊ mice), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
224
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 192 publications
(239 citation statements)
references
References 27 publications
9
224
6
Order By: Relevance
“…The CD5 + CD81 + pDCs express substantially less IRF7 mRNA than CD5 − CD81 − pDCs, which might explain their diminished type I IFN production. In contrast, these pDCs express a higher level of IRF5, a signaling factor in pDCs that can induce transcription of proinflammatory cytokines, chemokines, and costimulatory molecules, as well as IFNα/β (43)(44)(45)(46). This finding may explain their more abundant production of IL-6 and elevated expression of CD40, CD80, and CD86.…”
Section: Discussionmentioning
confidence: 37%
“…The CD5 + CD81 + pDCs express substantially less IRF7 mRNA than CD5 − CD81 − pDCs, which might explain their diminished type I IFN production. In contrast, these pDCs express a higher level of IRF5, a signaling factor in pDCs that can induce transcription of proinflammatory cytokines, chemokines, and costimulatory molecules, as well as IFNα/β (43)(44)(45)(46). This finding may explain their more abundant production of IL-6 and elevated expression of CD40, CD80, and CD86.…”
Section: Discussionmentioning
confidence: 37%
“…Conversely, IRF5 has been reported as a tumor repressor in breast cancer and negatively regulates CD24 expression, but similarly, no association with date has been shown between IRF5 and EMT to the best of our knowledge 15, 34. We also observed that IRF5 knockdown in preEMT H358 cells increased CD24 + cell subpopulation (from 0.6% to 4.1%, Fig.…”
Section: Discussionmentioning
confidence: 48%
“…85 However, a recent report from the same investigators showed that production of IFNa and IFNb in splenic macrophages as well as serum IFN levels in response to viral infections were markedly decreased in Irf5À/À mice, supporting the role of IRF5 in type I IFN production also in mice, although the contribution might be stimulation specific and cell type dependent. 86 Association of IRF5 gene polymorphisms with SLE Association of IRF5 intron 1 SNP with SLE In an effort to replicate the association of IRF5 rs2004640T with SLE, 64 Graham et al 87 genotyped four sets of SLE cases and controls from the United States, Spain, Sweden and Argentina (total of 1661 cases and 2508 controls) as well as 470 families with SLE. They found a significant increase of the T-allele frequency in the patients; overall, four-cohort analysis showed 60.4% in cases versus 51.5% in controls (P ¼ 4.4 Â 10 À16 ).…”
Section: Irf5 In Murine Lupusmentioning
confidence: 99%